Arsenic-Induced Oxidative Stress in Cardiac Tissue of Rats: Synergistic Effects of Folic Acid and Vitamin B\(_{12}\) - Bhattacharjee, Surajit; Pal, Sudipta (Challenges and Advances in Pharmaceutical Research Vol. 8, 2022)
The objective of the article is to elucidate the effects of folic acid and vitamin B12 individually or in combination on oxidative stress biomarkers in cardiac tissue of rats. Additive beneficial effect of vitamin B12 and folic acid against arsenic-induced oxidative stress in myocardial tissue was found in male Wistar rats. NaAsO2 exposure at a dose of 6 mg (i.p.)/kg b.w./day for one month exhibited significant decline in cardiac glutathione content associated with increased malondialdehyde production. Certain antioxidant enzyme activities such as SOD, catalase, glutathione-S-transferase, glutathione reductase were inhibited after arsenic exposure. Moreover, arsenic treatment significantly increased the nitric oxide production in cardiac tissue of rats. Folic acid (50 \(μ\)g/kg b.w./day) and vitamin B12 (1 \(μ\)g/kg b.w. /day) alone or in combination for the last 2 weeks of arsenic treatment exhibited distinct protective efficacies against arsenic mediated oxidative damage. It was further noted that combined exposure of folic acid and vitamin B12 exhibited synergistic beneficial effects against arsenic-induced oxidative stress in myocardial tissue.